The Influence of Motivation and Work Compensation on Employee Performance of PT Immortal Cosmedika Indonesia Palembang Branch - Idaman Putra (International Journal of Marketing & Human Resource Research, 2021)
This study aims to analyze the effect of motivation and work compensation on the performance of employees of PT Immortal Cosmedika Indonesia Palembang Branch. The data used are primary and secondary data obtained through questionnaires and interviews. The number of respondents in the study was 60 people. The analytical method applied in this study is the coefficient of determination analysis. The results prove that motivation (X1) has a positive effect on employee performance (Y). Compensation (X2) is also proven to have a positive effect on employee performance (Y). This research is useful for PT Immortal Cosmedika Indonesia Palembang Branch to improve employee performance through motivation and job compensation.